Methods of technology intensification for obtaining biomineral fertilizers and biogas from secondary raw materials - Ivanchenko, I.V. (Problems of Environmental Biotechnology, 2023)
It is recommended to use two methods of intensification of the technology of obtaining biomineral fertilizers and biogas from secondary raw materials, namely, microbiological activation using milk whey and preliminary hydrodynamic cavitation treatment of the initial components.